As performances de proximidade da Orquestra Sinfônica de Goiânia - Penna, Isabella de Barros (2024)
This research aims to answer the question: how do audiences appropriate the Goiânia Symphony Orchestra (OSGO's) proximity performances? Thus, it aims to understand the public's appropriation of the OSGO's proximity performances and to identify these proximity performances that the Goiânia Symphony Orchestra has adopted over the years, from its foundation to the present day, relating them to the implementation of cultural public policies. By proximity performances, we mean the actions performed by the OSGO, in dialogue with municipal cultural policies, in order to diversify the public and democratize the consumption of classical/erudite music in Goiânia. To this end, culture is seen as a resource, as proposed by Yúdice (2004). To this end, a bibliographical and documentary study will be carried out, using questionnaires and interviews, to understand the trajectory of this Orchestra and its attempts to appropriate public cultural policies that are close to the population of the city of Goiânia. The bibliography will be based on the concepts of Cultural Policies by anthropologist García Canclini (1987), as well as concepts of culture as a resource and what is understood as performativity through the cultural studies of George Yúdice (2004). Understanding through the concepts of cultural performances brought up by Victor Turner (1982) and Schechner (2002), to what would be the relationship of proximity performances raised by Carrijo and Satler (2019). As a result, we identified the proximity performances that the object of study of this research, the Goiânia Symphony Orchestra, has developed over the years, and we understood who its audience is today and how it has appropriated these proximity performances.